THE IMPACT OF MATERNAL BEHAVIOR ON PRENATAL CLASS PARTICIPATION - Herawati, Cucu; Hartini, Nonih Sri; Banowati, Lilis; Kristanti, Iin; Indragiri, Suzana; Mutiah, Dewi; Wahyuni, Nuniek Tri (Siklus : Journal Research Midwifery Politeknik Tegal, 2025)
Pregnancy classes are crucial for helping pregnant women address the physical and mental challenges they face, which can affect the birthing process. However, many women do not attend these classes. This research analyzes the factors influencing maternal behavior regarding participation in pregnancy classes.This quantitative study employs a cross-sectional approach, involving 403 pregnant women as subjects. A simple random sampling method was used to select 80 participants, with data collected through interviews. The Chi-Square test was utilized for data analysis.Findings indicate that 87.5% of pregnant women had low education levels, while 66.3% displayed good knowledge about pregnancy. Most participants (71.3%) reported inadequate facilities and infrastructure, though 66.3% received support from their husbands. Additionally, 66.3% of women were not actively involved in the classes. A significant relationship was found between education (p=0.010), knowledge (p=0.010), facilities (p=0.000), and husband's support (p=0.000) with participation in pregnancy classes. It is recommended that pregnant women actively engage in these classes voluntarily. Community health centers should enhance awareness to encourage participation, enabling early detection of pregnancy and childbirth complications.